Editorial — NOvation Forum II: «Reimagining Innovation for the Public Good» — Reflections from the II NOvation Forum - Bagattolli, Carolina; Brandão, Tiago; von Schomberg, Lucien (NOvation — Critical Studies of Innovation, 2025)
In a world increasingly captivated by the allure of technology and rapid innovation, the II NOvation Forum, held at the Federal University of Paraná (UFPR), in September 2024 (4-6th) stands as a critical and inspiring milestone. Under the theme «Reimagining Innovation for the Public Good», students, practitioners, and scholars from across the globe gathered to question the prevailing narratives of innovation and to explore alternative futures grounded in social justice, sustainability, and collective well-being. Building on the foundations laid during the inaugural Forum, the second edition reaffirmed NOvation's mission: to establish an interdisciplinary community around the study of innovation, scholar-led community, a slow-science research endeavour that critically examines innovation as a deeply political phenomenon. It called for a shift beyond the mere deployment of emerging technologies, embracing the social, historical, and ethical dimensions of innovation practices. More fundamentally, it challenged the ideology of "innovation-speak" (according to Vinsel and Russell 2020 book, «The Innovation Delusion») that pervades contemporary policy and academic discourse, inviting us to rethink who innovation serves and how it can truly contribute to the public good.